Developing Emotional Intelligence for Education Innovation in Schools - Anh, Nguyen Thi Tuyet; Huy, Nghiem Xuan (VNU Journal of Science: Education Research, 2022)
Nurturing emotion and evoking compassion or empathy for learners has been an important task of education. Of the four pillars of education for the 21 st century proposed by UNESCO, the two pillars (namely “learning to be” and “learning to live together”) are closely related to the matter of developing Emotional Intelligence (EI) for learners. The mission of education is therefore not only to impart knowledge and practice skills to students but also to help them develop their personalities, be rich in soul,  and contribute to the community. This article discusses issues related to the concept and the role of EI in their life, work, and future. It also analyzes other aspects such as organizing training, innovating teaching methods, and creating an educational environment to foster EI for learners in the Vietnamese higher education context.